Investigação da impulsividade pela Prova de Rorschach em policiais militares do Comando de Missões Especiais da Polícia Militar do Pará - GUEDES, Catia de Farias (Universidade Federal do Pará, 2014)
This dissertation arose from the desire to understand the presence of the variable of impulsiveness. The research project had led to the hypothesis that uniformed police personnel in the Special Missions Command would show responses of impulsiveness, based on findings in previous research using other testing instruments, such as the Palographic Test and the Wartegg Test. The characteristic of impulsiveness intrigued us because it is one of the criteria for rejecting candidates for the exercise of police functions. The purpose of using the Rorschach Test as an instrument of investigation was due to its adequacy for appraising the dynamics of the personality and because it is a projective technique. The method chosen was delineated quantitatively and qualitatively, and factors relevant to an investigation on impulsiveness carried special weight on the instrument. The subjects corresponded to 20% of the total members of the troop studied and were chosen on the basis of the function they exercised and the length of time they had been in the unit, as well as other criteria. The findings led us to refute the initial hypothesis; it was seen that the impulsiveness detected in the earlier study could be better classified as readiness and immediatism of attitudes. Even with a high Imp rate, the group showed capacity for satisfactory interior control to prevent impulsiveness from becoming prejudicial or interfering in their operational functions. The possibility of investigating a specific score for the type of police activity carried out by this group or by others in similar operations is discussed. In the case at hand, even though 80% of the group did not correspond to the expected results in the formula on impulsiveness, other factors related to the responses of Color and Shape failed to confirm the formula in any of the subjects. This leads to the conclusion that impulsiveness is present in the group but it does not appear as prejudicial, but rather, contained.